PEMANFAATAN HASIL FERMENTASI LIMBAH CAIR TEH HIJAU PADA FREKUENSI PENYIRAMAN YANG BERBEDA TERHADAP PERTUMBUHAN BIBIT KARET (Hevea brasiliensis Mull. Arg) - Retno Muningsih; Farhan Wardhana Majing (MEDIAGRO, 2019)
ABSTRACT This research aimed to know the differences influence the frequency of watering fermentation liquid waste green tea on early growth of rubber plant seed. This research method using Randomized Complete Block Design (RCBD) non factorial, i.e. the granting of fermentation liquid waste green tea with a dose of 10 ml/poly bag with 3 treatment. As for the extent of the treatments given are control (P0), the frequency of watering every two weeks (P2), the frequency of watering every four weeks (P4). Each treatment was repeated five times so that there are 15 units of the experiment. Each unit is comprised of 1 trial crops so that there is a total of 15 plants. The giving of liquid organic fertilizer from waste liquid fermented green tea can enhance plant growth include rubber, i.e. plant height, number of leaves, green leaves, heavy wet and dry long & root plant rubber. On treatment of P2 (the frequency of watering every two weeks) show the highest results and good than P0 treatment (control) and P4 (the frequency of watering every four weeks). Keywords: fermentation, tea liquid waste, liquid organic fertilizer.